DT-13 Inhibits Proliferation and Metastasis of Human Prostate Cancer Cells Through Blocking PI3K/Akt Pathway - Wang, Zhengming; Wang, Yingying; Zhu, Shan; Liu, Yao; Peng, Xin; Zhang, Shaolu; Zhang, Zhe; Qiu, Yuling; Jin, Meihua; Wang, Ran; Zhong, Yuxu; Kong, Dexin (Frontiers in Pharmacology, 2018)
DT-13, a saponin monomer 13 from the dwarf lilyturf tuber, was reported to exhibit anti-inflammatory, hepatoprotective, cardioprotective as well as antitumor activities in a number of tumor cells. Prostate cancer is the second leading cause of cancer death in males, discovery of novel antitumor drug for therapy of prostate cancer is expected. Aiming to evaluate whether DT-13 could become a candidate to treat prostate cancer, we recently investigated the antitumor effect of DT-13 on human prostate cancer cells and the underlying mechanism. DT-13 was found to effectively inhibit proliferation and metastasis of prostate cancer PC3 and DU145 cell lines in a dose-dependent manner. Treatment by DT-13 resulted in a mitochondria-mediated apoptosis, which was accompanied by the chromatin condensation and nuclear shrinkage in the prostate cancer cells. Moreover, DT-13 caused remarkable upregulation of Bax, Bad, Cytochrome C, cleaved -caspase 3, -caspase 9 and -PARP, in contrast to the downregulation of Bcl-2. Nevertheless, no obvious change in intracellular ROS level was observed after DT-13 treatment. We further demonstrated that DT-13 could inhibit PC3 cell metastasis in which suppression of Integrinβ1 and MMP2/9 might be involved. Western blot analysis indicated DT-13 significantly decreased the phosphorylation of PDK1, Akt, mTOR as well as p70S6K, suggesting the pro-apoptotic and anti-metastatic effects of DT-13 on prostate cancer cells might be attributed to the blockade of PI3K/Akt pathway. Collectively, our findings suggest DT-13 is worthy of further investigation as a drug candidate for the treatment of prostate cancer.